Performance Evaluation of a Single Frequency GPS Device for Measuring Ionospheric Total Electron Content - Pharinya Phothila; Thanapon Keokhumcheng; Prasert Kraisi; Chollada Pansong; Nitipat Buakao; Prasert Kenpankho (My University, 2025)
The Global Navigation Satellite System (GNSS), particularly GPS, plays a crucial role in communication, navigation, and geophysical studies. However, fluctuations in Total Electron Content (TEC) in the ionosphere affect signal accuracy, causing delays and positioning errors. While dual frequency GPS receivers provide precise TEC measurements, their high cost remains a limitation. Single frequency receivers offer a cost-effective alternative, and research suggests they can still provide valuable TEC data with appropriate analysis. This study evaluates the performance of the ionosphere single frequency GPS total electron content measurement device using GPS signal delay data from 2004 to 2023. Data processing was conducted using Python on a Raspberry Pi, incorporating seasonal ionospheric adjustments. The device was assessed by five experts across four criteria, receiving an average score above 4.00. Additionally, a training program was conducted with 20 participants, all of whom successfully installed and operated the system more than 60 points, with a $100 \%$ success rate. The participants’ satisfaction level averaged above 4.50, classified as the highest rating. The findings confirm the feasibility of using low-cost single frequency GPS receivers for TEC studies, enhancing accessibility to ionospheric research.
Keywords: Ionosphere and magnetosphere dynamics; Magnetic Field Sensors Techniques; GNSS positioning and interference